Biaxial failure response of composite laminates - Goh, Wee Ter (2014)
In this report, a modified arcan test-setup is designed and fabricated to investigate the fracture behaviour of glass fibre reinforced epoxy matrix composite (GFRP) laminates in mode I (tensile) loading, mode II (shear loading) as well as mixed-mode loading. Arcan test jig is chosen as this setup allows the extracting of fracture properties in various modes using only only one shape and size of specimen. Bi-directional and uni-directional specimens are used for the tests in the study.